THE ECONOMIC IMPACT OF TOURISM DEVELOPMENT IN PENGLIPURAN VILLAGE, BANGLI - Made Novita Dwi Lestari (UHN IGB Sugriwa Denpasar, 2023)
Penglipuran Traditional Village, is one of the Cultural Tourism Objects, located in Bangli Regency. Penglipuran Village has been a Tourism Village since 1993. Since then this village has been listed as one of the Tourism Villages in Bali by offering a beautiful scenery. Penglipuran Village as a tourist village, the local community directly and indirectly gets economic benefits, However, in its development, the Penglipuran Village community showed a proactive attitude to support the program launched by the government to make Penglipuran Village a Tourism Village.The government needs to revise the distribution of proceeds from the sale of entrance tickets given by the Penglipuran Traditional Village, because the distribution that is currently being received by the Villagers feels that there is injustice, so as not to cause problems in the future, this is urgent to consider and negotiate with the Penglipuran Traditional Villagers